2022
DOI: 10.15562/bmj.v11i2.3436
|View full text |Cite
|
Sign up to set email alerts
|

Microbial blood culture patterns and antibiotic susceptibility in pediatric febrile neutropenia at Sanglah General Hospital Bali

Abstract: Background: Febrile neutropenia is defined as a fever with a temperature more than or equal to 38.3°C in two measurements within 24 hours and accompanied by severe neutropenia (≤500/μL). Gram-positive bacteria have been the most common cause of febrile neutropenia in children for the previous two decades. However, the contradiction in some studies reported that gram-negative bacteria were the main pathogens causing infection. Because there are differences and shifts in the bacterial spectrum, information on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…35 Contrary, Bian et al reported that topical Doxycycline 0.1% on ocular alkali burn did not reduce TIMP-1 expression. 12,30,36 This might be because TIMP-1 works in two mechanisms: MMP-dependent mechanism and the MMP-independent mechanism. In MMPdependent mechanism, TIMP reversibly blocks MMP activity with a stoichiometric ratio of 1:1, therefore reducing ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Contrary, Bian et al reported that topical Doxycycline 0.1% on ocular alkali burn did not reduce TIMP-1 expression. 12,30,36 This might be because TIMP-1 works in two mechanisms: MMP-dependent mechanism and the MMP-independent mechanism. In MMPdependent mechanism, TIMP reversibly blocks MMP activity with a stoichiometric ratio of 1:1, therefore reducing ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Firm size in its effect on audit delay according to (Miradhi dan Juliarsa 2016) explained that the size of the company can be seen through total assets . Companies with large total assets generally have good quality control which has an impact on the length of time the auditor needs to audit this according to research conducted by (Sartim 2018); (Karang et al 2016).…”
Section: Introductionmentioning
confidence: 99%